The Role of Management School’s Committees in the Implementation of Public Elementary School Education - Rozikin, Rozikin; Ahyani, Nur; Eddy, Syaiful (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this research is to investigate the role of school committee empowerment management in a public elementary school unit in Plakat Tinggi District, Musi Banyuasin Regency. The qualitative descriptive technique is used in the research process, which includes observation, interviews, and documentation. The Chairperson/Management of the School Committee, Principal, Teachers, Parents/Guardians of Pupils, and Students from Plakat Tinggi District, Musi Banyuasin Regency served as research subjects. The findings (1) school committees have a planned program based on the school’s requirements, requests, and ideas; (2) In comparison to the program for establishing the Organizational Structure and Work Program, the program for producing the Statutes and Bylaws is pretty good. (3) The Empowerment Management of the School Committee as Fundraising and Educational Resources from the Community and in Following Up Aspirations, Ideas, Complaints, Suggestions, and Criticism from the Community and Student Guardians is quite good in relation to the School Committee fundraising and carrying out its functions and duties following up on complaints, suggestions, criticisms, and aspirations from students, parents/guardians, and the community.